(untitled) (Bangladesh Journal of Zoology, 2017)
The influence of tea mosquito bug (Helopeltis theivora) infestation on the physiological and biochemical changes in tea leaves as well as quality parameters of the made tea was investigated. Results revealed that physiological parameters such as polyphenol, chlorophyll a and b, carotenoids, catechins, reducing sugar and antioxidant activity reduced when the shoots are infested by tea mosquito bug. Black tea prepared from Helopeltis infested shoots contained significantly lower amount of theaflavin and thearubigin ratio, highly polymerized substances, total liquor colour, colour index, caffeine and lipid than that of uninfested fresh tea leaves. The infestation of tea mosquito bug significantly reduced the physiological parameters of tea leaves and quality parameters of made tea that hamper the quality of drinking tea. Bangladesh J. Zool. 44(2): 197-207, 2016